The pharmacokinetics and pharmacodynamics of alogliptin in children, adolescents, and adults with type 2 diabetes mellitus - Dudkowski, Caroline; Tsai, Max; Liu, Jie; Zhao, Zhen; Schmidt, Eric; Xie, Jeannie (European journal of clinical pharmacology, 2017)
Purpose The aim of this study is to determine the pharmacokinetics (PK) and pharmacodynamics (PD) of a single 12.5- or 25-mg dose of alogliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, in pediatric (children and adolescents) and adult subjects with type 2 diabetes mellitus (T2DM). Methods A randomized, open-label, multicenter study was conducted in pediatric and adult subjects. Subjects in two pediatric groups (children and adolescents) were randomized 1:1 to receive a single oral dose of alogliptin 12.5 or 25 mg, respectively; all gender- and race-matched adult subjects received alogliptin 25 mg. Blood and urine samples were collected at prespecified time points for PK/PD analyses. A PK/PD model was developed using data from the study for steady-state simulations. Safety was also assessed. Results In pediatric subjects receiving the 25-mg dose, the mean alogliptin peak plasma concentrations (C max ) and AUC 0-inf values were 26 and 23% lower, respectively, than in adults receiving the 25-mg dose, but maximum observed DPP-4 inhibition effect (E max ) and AUEC 0–24 values were similar to those in adults. In pediatric subjects receiving the 12.5-mg dose, the mean alogliptin C max and AUC 0-inf values were 58 and 54% lower, respectively, than those in adults, hence E max and AUEC 0–24 values were also lower by 11 and 17%, respectively. The PK/PD model simulated data were consistent with study results. No safety concern was found. Conclusions A 25-mg dose of alogliptin in pediatric subjects achieved alogliptin exposures and DPP-4 inhibition similar to those in adult T2DM patients without safety concerns; therefore, this dose is recommended for a pediatric phase 3 trial.